Preliminary Survey on Knowledge, Attitudes, and Practices about the COVID-19 Pandemic among Residents in North Central Nigeria - Elijah Edache Ehoche; Johnson Adejoh; Joseph Idoko; Chijioke Madu (Borneo Journal of Pharmacy, 2020)
A preliminary survey on the knowledge, attitude, and practice of the COVID-19 pandemic among residence in North Central Nigeria, was conducted. An anonymous electronic network sampling survey designed by e-survey was employed. The result showed that on the level of knowledge and practice, 76.83% opined that people may be sick for 1-14 days without developing the symptoms. On the viral transmission, 94.41% agreed that the transmission of the virus can be through direct contact with contaminated surfaces through eyes, nose, and mouth, as well as 78.35%, responded that the virus doesn't penetrate the skin. More so 92.04% of the respondents showed that older and sick people are more vulnerable to the disease with 98.86% showing that the most common symptoms may include fever, tiredness, dry cough, and sometimes difficulty in breathing. Only 24.43% asserted that COVID-19 cannot be transmitted through social gatherings, going put often, making direct physical contact with people. Meanwhile, 21.02% showed COVID-19 is a punishment for immoral behavior. On the rate of the outbreak, 94.32% said it is scary. Only 55.11% asserted approval of the control approach by the government. However, 82.29% would agree with the response of the masses to government measures to control the spread. On the way forward, 98.87% advised the need for more research and 87.08% would approve of vaccination against the disease. This implies that the respondents have a good level of knowledge and practice about COVID-19 and necessary adjustments are needed to control or manage the spread of the pandemic.